Environmental Factors Associated with the Upstream Migration of Fall‐Run Chinook Salmon in a Regulated River. (21st December 2016) - Peterson, Matthew L.; Fuller, Andrea N.; Demko, Doug
Abstract: We examined upstream migration patterns of adult Chinook Salmon Oncorhynchus tshawytscha in relation to environmental factors and two management actions (installation of a rock barrier at a distributary and managed pulse flows). Data was collected using a portable resistance board weir and a Vaki Riverwatcher system that provided accurate daily counts of fall‐run Chinook Salmon on their spawning migration. Akaike's information criterion and multimodel inferential approaches, as well as generalized additive models, were used to assess the relative influence of water temperature, flow, moon illumination, weather, operation of a rock barrier, and managed pulse flows to explain the magnitude of daily counts and proportions of Chinook Salmon observed at the weir. Over the 12‐year study period (2003–2014), we observed 38, 206 Chinook Salmon. The installation of a rock barrier in the lower reaches of the San Joaquin River had positive and consistent influences on daily counts in the years it was installed. Although managed pulse flows to stimulate upstream migration have been used since the early 1990s, our analyses found managed pulse flows only appeared in the top generalized linear models in 2 of the 11 complete years of data analyzed. Managed pulse flows resulted in immediate increases in daily passages, but the response was brief and represented a small portion of the total run. A strong nonlinear response between migratory activity and discharge levels was observed for Chinook Salmon, indicating no additional increase in daily counts when pulse flows exceeded 20 m 3 /s. Current management requirements in the Stanislaus River exceed this level and adjustment should be considered based on the findings of this study, particularly given the need to balance beneficial uses of a limited water supply. This study provides a scientific approach to determine biologically relevant flow prescriptions for upstream migration of fish in regulated streams. Received February 5, 2016; accepted September 15, 2016Published online December 21, 2016